Is There a War Party? Party Change, the Left–Right Divide, and International Conflict - Bertoli, Andrew; Dafoe, Allan; Trager, Robert (Sage, 2018)
Are leaders from certain parties particularly likely to engage in military conflict? This question is difficult to answer because of selection bias. For example, countries may be more likely to elect right-wing leaders if their publics are more hawkish or if the international system is particularly dangerous. Put simply, who comes to power is not random, which makes causal inference difficult. We overcome this problem by using a regression discontinuity design. Specifically, we look at close presidential elections that were essentially “tossups” between two candidates. We find that electing right-wing candidates increases state aggression. We also find that electing candidates from challenger parties makes countries much more likely to initiate military disputes, particularly in the first year of the new leader’s term. This result is consistent with other studies that find that the likelihood of state aggression increases following major leadership transitions.
Keywords: International conflict; 59 Ciencia Política::5901 Relaciones internacionales; ODS 16 - Paz, justicia e instituciones sólidas